Chloroquine is therapeutic in murine experimental model of paracoccidioidomycosis - Dias-Melicio, Luciane Alarcao; Calvi, Sueli Aparecida; Bordon, Ana Paula; Golim, Marjorie de Assis; Serrao Peracoil, Maria Terezinha; Victoriano Campos Soares, Angela Maria (Blackwell Publishing, 2007)
Chloroquine, due to its basic properties, has been shown to prevent the release of iron from holotransferrin, thereby interfering with normal iron metabolism in a variety of cell types. We have studied the effects of chloroquine on the evolution of experimental paracoccidioidomycosis by evaluating the viable fungal recovery from lung, liver and spleen from infected mice and H2O2, NO production, tumor necrosis factor-alpha (TNF-alpha), interleukin (IL)-6, IL-10 levels and transferrin receptor (TfR) expression from uninfected and infected peritoneal macrophages. Chloroquine caused a significant decrease in the viable fungal recovery from all organs tested, during all periods of evaluation. Peritoneal macrophages from chloroquine-treated infected mice showed higher H2O2 production and TfR expression, and decreased levels of NO, endogenous and stimulated-TNF-alpha, IL-6 and IL-10 during the three evaluated periods. However, despite its suppressor effects on the macrophage function, the chloroquine therapeutic effect upon murine paracoccidioidomycosis was probably due to its effect on iron metabolism, blocking iron uptake by cells, and consequently restricting iron to fungus growth and survival.
Keywords: Paracoccidioides brasiliensis; chloroquine; iron; hydrogen peroxide; nitric oxide; cytokines